The effect of land cover forest on fluctuations in availability of water in the Batutegi Dam, Lampung, Indonesia. Issue 1 (1st May 2022) - Artika, E; Yuwono, S B; Banuwa, I S; Setiawan, A; Bakri, S; Wahono, E P
Abstract: The Sekampung Hulu watershed has an important role in Lampung Province, as a catchment area for the Batutegi Dam with the main function as a supplier of irrigation water therefore it is very dependent on the availability of water (inflow). The inflow fluctuation is one of the indicators to determine the hydrological condition. The relationship between forest cover and inflow fluctuations was obtained from forest cover analysis on Landsat images using the object-oriented classification (OOC) method and inflow fluctuation analysis, followed by regression analysis between them. The results showed that the total inflow value in 2005 - 2020 is fluctuated with the lowest total inflow value of 6862.243 m 3 /S in 2015 and the highest value of 9296.141m 3 /S in 2020. Inflow fluctuation from 2005-2020 was included in the low and moderate category. The condition of forest cover in the Sekampung Hulu watershed in 2005-2020 has increased and decreased in each period. Analysis of the relationship between forest cover and inflow fluctuations is a significant with a p-value of 0.092 with a 90% confidence level. The results showed that the condition of forest cover greatly affects the stability of the water availability of the Batutegi Dam.